2006
DOI: 10.3766/jaaa.17.4.5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Antioxidant N-acetylcysteine (NAC) in Protecting Ears Exposed to Loud Music

Abstract: Antioxidants have been reported to be effective in reducing acoustic trauma in animal models but have not been studied in humans. In this study, the antioxidant N-acetylcysteine (NAC) was evaluated to determine if it would reduce temporary changes in auditory function as a result of exposure to loud music in humans. Pure-tone thresholds and distortion product otoacoustic emissions (DPOAEs) were collected in 31 normal-hearing participants, using a randomized, double-blind, placebo-controlled design, before and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
60
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(67 citation statements)
references
References 60 publications
2
60
2
Order By: Relevance
“…In a randomized double-blind placebo-controlled trial, 31 volunteers either received oral NAC (900 mg, single dose) or placebo 1 h prior to attending a nightclub for 2 h. Pure tone audiometry and DPOAE testing were performed on all patients prior to and after the nightclub noise exposure. The results of this study did not demonstrated any significant differences in the temporary threshold shift that resulted from the nightclub noise exposure between NAC treatment and the placebo groups; however, this study did not evaluate these 2 groups for PTS [65]. The result of this is consistent with the results obtained from many animal studies that have found the otoprotective effects of NAC evident primarily on PTS, but not on temporary threshold shift [66,67,68].…”
Section: Antioxidantssupporting
confidence: 82%
“…In a randomized double-blind placebo-controlled trial, 31 volunteers either received oral NAC (900 mg, single dose) or placebo 1 h prior to attending a nightclub for 2 h. Pure tone audiometry and DPOAE testing were performed on all patients prior to and after the nightclub noise exposure. The results of this study did not demonstrated any significant differences in the temporary threshold shift that resulted from the nightclub noise exposure between NAC treatment and the placebo groups; however, this study did not evaluate these 2 groups for PTS [65]. The result of this is consistent with the results obtained from many animal studies that have found the otoprotective effects of NAC evident primarily on PTS, but not on temporary threshold shift [66,67,68].…”
Section: Antioxidantssupporting
confidence: 82%
“…Nacetylcysteine (NAC), a glutathione precursor and ROS scavenger, has been effective in reducing PTS in noise-exposed guinea pigs (Ohinata et al, 2003;Duan et al, 2004) and chinchillas (delivered in combination with salicylate, see Kopke et al, 2000), with no effect on TTS in man (Kramer et al, 2006) or rodents (Kopke et al, 2000;Duan et al, 2004). Given that a major determinant of GSH level is bioavailable cysteine, and that cysteine can be derived from methionine, an alternative strategy has been pre-treatment with D-methionine.…”
Section: Endogenous Antioxidant Defense Against Nihlmentioning
confidence: 99%
“…In 2011, Lindblad and colleagues reported that oral administration of NAC was capable of protecting the cochlea from loss of nonlinearity (the peculiar transductive mechanism of the inner ear that makes a wide dynamic range possible) from impulse noise (in this case, soldiers exposed to fi rearm discharge noise) (Lindblad et al 2011 ). In contrast, Kramer et al and Lin et al have reported less successful attempts toward otoprotection from NAC administration in humans subject to noise (Kramer et al 2006 ). Lin and colleagues also tested NAC as an otoprotectant after industrial noise exposure (Lin et al 2011 ).…”
Section: Nihl and Antioxidantsmentioning
confidence: 99%